Upgrading and development of computer automation and interface software of electrical measurement system - Ong, Clement Yee Chee (2018)
This project is to review the methodology to develop a user interface for the Agilent 4155b on the LabVIEW programming software platform with communication established through the General Purpose Interface Bus (GPIB) interface. The user interface will be used to measure and plot the transfer characteristics (Ids vs Vgs) and the output I-V characteristics (Ids vs Vds) of a transistor. The achieved results will be included in this report and it will be used to obtain the On/Off ratio, Threshold Voltage and Mobility of the transistor. Detailed breakdown of the LabVIEW code constructed for the user interface will also be studied in this report.